EVALUASI PERTUMBUHAN TANAMAN SENGON DARI BERBAGAI ASAL SUMBER BENIH (PROVENANCE) PADA UMUR 3 TAHUN (Di PT Green Forest Indonesia, Desa Mentigi, Kecamatan Membalong,Kabupaten Belitung) - , KADEK ANDRY PRADIPTA; , Ir. Sri Danarto, M.Agr. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sengon (Parasenthisfalcataria) is one of woodsâ plants that have characteristic fast growing. Generatively the activity of sengonsâ propagation needs seed which has good quality and had been test. Effort to get the feed that has a good quality bye PT Green Forest Indonesia(Indonesian green forest company)through provenance experiment. The research of sengon provenancesâ experiment is to figure out provenances âgrowth which suitable to environmentsâ condition in Mentigi, Belitung. Designing plant of provenancesâ experiment was evaluated square plot form with a set of complete random (CRD). There are 25th feed from Java and outside of Java. Compartment provenancesâ experiment used repeating method during 1-17th. The data get included: life percent, tall and diameter. The data analysis used descriptive quantitative method refer to levelsâ repeat R-4, R-7, and R-10 with organized the average. The organized based on diameter of average on R-4, R-7, and R-10 some provenance stability occupied on high level. But with the organized that uses of the average of life percent make a significant shift. The provenance that come from Java island showed that the average percent life and high, however the diameter average lower than provenance from outside of Java. In every plot of provenances Ternate Salamadaha 002 occupied first position in diameter of average (13.63-16.55 cm) and high (10.13-10.99 m), but low life of percent (27.78-37.78 %). Provenance Malang Ngantang 002 showed the diameter of average (12.68-15.88 cm) and high (9.29-9.57 m) however showed the highest life of percent (66.7-80.00). Determine of provenance Malang Ngantang 002 as a sources of seed more benefit from the risk of side plants success.